IDENTITAS LOKAL RADIO BERJARINGAN MNC TRIJAYA FM MELALUI PROGRAM NGADU BOKO - Slamet Parsono (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
The purpose of this study is to determine the extent to which MNC Trijaya FM as a networked radio in the city of Bandung is able to represent the values of local identity of a region. This research uses a descriptive qualitative methodological approach, and a theoretical approach to Critical Discourse Analysis (AWK) from Norman Fairclough. The data of this study are fragments of the Ngadu Bako MNC Trijaya FM program discourse and key informant in-depth interviews. Based on the research, the following results are obtained: first, the efforts made by MNC Trijaya FM are not interpreted as an ideology that the characteristics of local identity are a culture that must be raised, not imaged as a weak culture. Second, the analysis of the practice of discourse focuses on how the discourse is produced and consumed. The production of this discourse is closely related to the ideology of the management of Trijaya FM MNC, talkshow resource persons, and actions to be achieved. As a networked radio, MNC Trijaya FM has not been able to fully represent local identity through the Ngadu Bako program. Third, the discourse produced is influenced by the textual dimension, the practice of discourse, and sociocultural practices.